Features of coxitis treatment in patients with ankylosing spondylitis - E. M. Agafonova; T. V. Dubinina; A. B. Dyomina; D. G. Rumyantseva; Sh. Erdes (Современная ревматология, 2018)
The hip joint damage (HJD) coxitis is a characteristic manifestation of ankylosing spondylitis (AS). Treatment policy for coxitis in this disease has not been worked out today. There are a few studies evaluating the efficacy of tumor necrosis factor-α (IFN-α ) inhibitors in these patients. Coxitis treatment with disease-modifying antirheumatic drugs (DMARDs) is under study.The paper describes three clinical cases of patients with AS and coxitis, in two of whom combined therapy with nonsteroidal anti-inflammatory drugs (NSAIDs), DMARDs, and IFN-α inhibitors produced a fairly rapid positive effect in reducing inflammatory changes in HJD as evidenced by magnetic resonance imaging; moreover, there was no x-ray progression. It can be assumed that there is a so-called window of opportunity when no irreversible structural changes in HJD occur during timely initiated therapy with biological agents (BAs).Our findings suggest that further investigations are needed to clarify the effects of DMARD and combination therapy using DMARD and BAs in combination with NSAIDs.